Remineralization Potential of a Modified Eggshell–Titanium Composite-Scanning Electron Microscope Study - Onwubu, Stanley Chibuzor; Mdluli, Phumlane Selby; Singh, Shenuka; Bharuth, Vishal (European Journal of Dentistry, 2019)
Objectives This article reports the remineralization potential of a modified eggshell–titanium dioxide (EB-TiO2) composite in the management of DH.Materials and Methods The prepared composite was further characterized using different techniques such as Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM), and field scanning electron microscopy (FSEM) to establish the modification. Forty freshly extracted bovine anterior teeth were used to evaluate the dentin tubule remineralization potential of EB-TiO2. Each tooth was sectioned mesiodistally to obtain dentin blocks. The dentin blocks were subsequently agitated in 4% wt. citric acid for 2 minutes to simulate sensitive tooth. Each dentin block was randomly assigned to five groups, namely Group 1: untreated, Group 2: EB alone, Group 3: EB-TiO2 treated, and Group 4: Colgate Sensitive, and Group 5: Sensodyne treated (n = 8) that were then subjected to remineralization protocol.Results Both the XRD and FTIR images confirm the surface medication of EB-TiO2. The TEM revealed a nonhomogeneous structure with an average particle size of 65 nm. FSEM further was used to observe the remineralization capabilities of the samples. The FSEM image of the dentin specimens treated with EB-TiO2 shows complete remineralization of the dentin tubules, which remain intact postacidic exposure.Conclusions This study confirmed that EB-TiO2 composite effectively remineralizes dentin tubules. More so, the composite could be a cheaper and more efficient therapy material in the management of DH.
Keywords: dentin hypersensitivity; eggshell; remineralization; titanium dioxide